„Lássatok hozzá, és építsétek föl Istennek, az Úrnak szentélyét” (A Debreceni Református Egyetemi Templom építésének története) - Dezső, Kinga (Gerundium, 2018)
„Rise up and Build the Sanctuary of the Lord God, so that you may bring the Ark of the covenant of the Lord.” – The History of the Construction of the Reformed University Church in Debrecen. In this essay I try to find the answer to the question of what the main cause of the structure of the University Church was and which were the most relevant stages of the construction. After launching the university in Debrecen, the undergraduates, the professors and the local citizens established a claim to engender a place of worship where they could get an opportunity to inward edification. The negotiations about the church to be constructed began in the 1910’s, after all the quartercentenary of the Reformed College gave the handle for the church’s structure. The University Church was built in vicissitudinous ways and it came up against a lot of difficulties during the second half of the twentieth century. Consequently this fact encumbers the researching of the building’s history. However, the history of construction is trackable by the eight boxfuls of sources of the Archives of the Transtibiscan Reformed Church District.